Mediation function brand loyalty on the effects of brand image and price to customer satisfaction - Abubakar, Arinal Haq; Sugito, Pudjo (Faculty of Economics and Business Mulawarman University, 2019)
The rapid increase of technology development opens the opportunity to compete freely especially for product smartphone that grows rapidly according to their excellence, uniqueness and characteristic or distinctive features. The purpose of the study was to investigate the effects of brand image and price to customer satisfaction through brand loyalty on smartphone Samsung study toward the users of smartphone Samsung in Malang city. The sample used is 60 respondents. The analysis used the inner and outer model test from SEM-PLS, to test the hypothesis was used result analysis from the bootstrapping test. The results show that brand image, price, and brand loyalty have positive significant effects on customer satisfaction and the Brand image has a positive significant effect on Brand loyalty while price does not have a significant effect to brand loyalty. Management Samsung smartphone should pay more attention to the price to improve brand loyalty from the customer.